Strategic global repositioning and the future economic development of Jamaica : the role of services - Bernal, Richard L ([s.n.] [S.l.], 1995)
Examines trends in the current global environment which have implications for Jamaica e.g. globalisation of production and finance, trade blocs and erosion of preferential trade agreements. Posits that a new development strategy will be required for Jamaica in order to surmount the events and trends now taking place at the global level. Opines that it would require proactive adjustment and strategic repositioning in the global economy. Looks at the role of services e.g. information processing and tourism. Identifies the advantages Jamaica has for service exports.